Effects of acute and chronic heat stress on the performance, egg quality, body temperature, and blood gas parameters of laying hens - Barrett, Nathaniel W.; Rowland, Kaylee; Schmidt, Carl J.; Lamont, Susan J.; Rothschild, Max F.; Ashwell, Chris M.; Persia, Michael E. (Poultry science, 2019)
The goal of this experiment was to measure the physiological response of individual laying hens exposed to heat stress (HS). Performance, egg quality, body temperature (BT), and blood chemistry of laying hens were individually recorded before and after various intervals of daily cyclic HS. In total, 407 18-week-old W-36 parent-line laying hens (Hy-Line International, Dallas Center, IA) were housed individually in battery cages. After an acclimation period, baseline data were collected from 22 to 24-wk before the hens were subjected to a daily cyclic HS consisting of 7 h at 35°C returning to 30°C for the remaining 17 h/D from 24 to 28-wk of age. Eggs were collected and individually weighed daily. Feed intake (FI), egg production (EP), egg weights, egg mass, BW, and feed efficiency (FE) (g egg/kg FI) were calculated over 2-wk time periods. Eggs were collected for quality assessment the day before HS began, the 2nd day of HS, and on a weekly basis throughout the 4-wk HS. Blood was collected and BT measured the day before heat HS was initiated, on the first day of HS, and again at 2 and 4-wk of HS. Blood PCO2 and iCa decreased, and blood pH increased within 4 to 6 h of HS (P ≤ 0.01). Shell weights decreased with acute HS, possibly due to the reduction in blood iCa (P ≤ 0.01). After 4-wk of HS the blood pH returned to pre-HS levels but iCa remained decreased (P ≤ 0.01). Shell weights remained low and Haugh units decreased after 2 and 4-wk of HS (P ≤ 0.01). Feed efficiency was increased and FI, EP, and BW decreased by 2-wk of HS and remained low through 4-wk (P ≤ 0.01). The cyclic HS had a significant effect on the performance, egg quality, and blood chemistry over the 4-wk HS.